Immunoglobulin G4 in primary Sjögren’s syndrome and IgG4-related disease - connections and dissimilarities - Maslinska, Maria; Kostyra-Grabczak, Kinga (Frontiers in Immunology, 2024)
Primary Sjögren’s syndrome (pSS) is an autoimmune disease, with B cell hyperactivation and autoantibody production as its immunological hallmarks. Although the distinction between immunoglobulin G4-related disease (IgG4-RD) and pSS, based on the presence or absence of certain autoantibodies, seems easy to make, possibility of elevated serum IgG4 concentration and often similar organ involvement may lead to a misdiagnosis. The increased serum concentration of IgG4 in IgG4-RD is not clearly linked to the pathogenesis of IgG-RD and it has been suggested that it may constitute just an epiphenomenon. The aim of this article is to discuss the presence of IgG4 in pSS and IgG4-RD and its potential significance for these two diseases.